Republic of Kazakhstan : Technical Assistance Report-Scanner Data for CPI Mission. - International Monetary Fund. Statistics Dept.. (Washington, D.C. : International Monetary Fund, 2022)
The purpose of the mission was to assist the Bureau of National Statistics of the Agency for Strategic Planning and Reforms of the Republic of Kazakhstan (BNS) with continuing its modernization of the Consumer Price Index (CPI). This was the first technical assistance (TA) mission to Kazakhstan on scanner data (SD). The mission was delivered remotely.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Kazakhstan, Republic of